Influence of basalt fiber on physical and mechanical properties of treated recycled aggregate concrete - Dilbas, Hasan; Cakir, Ozgur (ELSEVIER SCI LTD, 2020)
This paper investigates the effect of the treatment methods on the physical and the mechanical properties of recycled aggregate concrete (RAC). The optimized Ball Mill Method (oBMM) and the incorporation of basalt fiber (BF) in concrete were employed as treatment process and the combination of oBMM and BF were utilized in this experimental study. It was intended using the treatment methods that the application of oBMM on recycled aggregate (RA) cleaned the most part of attached old mortar (AOM) content in RA and the incorporation of BF in concrete eliminated the adverse effects of remaining AOM in treated RA (tRA) strengthening mortar phase of concrete. Hence, to observe the improvement impact of treatment on the performance of concretes, twenty-eight concrete series including natural aggregate (NA), 20-40-60% RA and 20-40-60% tRA with 0-0.25-0.50-1.0% BF were produced in the laboratory. The physical and the mechanical tests were conducted on concrete specimens at the age of 28 days. According to the test results, although the physical properties were negatively affected by the incorporation of RA and tRA with/without BF in concrete, the mechanical properties of RACs and tRACs were improved by the incorporation of BF. Besides, the impact of treatment were significantly observed, especially for higher rates of RA (60%). The optimum proportion of BF was found as 0.50% BF with 60% tRA regarding compressive strength test results only. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Basalt fiber; Treated recycled aggregate; Physical properties; Mechanical properties; Fracture parameters; SILICA FUME; FLY-ASH; PERFORMANCE; BEHAVIOR; COARSE; RUBBER; ENERGY; Construction & Building Technology; Engineering; Materials Science